2012
DOI: 10.1007/s10545-012-9485-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tetrahydrobiopterine (BH4)‐responsive alleles among Austrian patients with PAH deficiency: comprehensive results from molecular analysis in 147 patients

Abstract: Phenylketonuria (PKU, MIM 261600) is an autosomal recessive disorder caused by mutations of the phenylalanine hydroxylase gene (PAH, GenBank U49897.1, RefSeq NM_000277). To date more than 560 variants of the PAH gene have been identified. In Europe there is regional distribution of specific mutations. Due to recent progress in chaperone therapy, the prevalence of BH4-responsive alleles gained therapeutic importance. Here we report the mutational spectrum of PAH deficiency in 147 unrelated Austrian families. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
3
12
1
Order By: Relevance
“…Unlike recent studies conducted in European PKU patients, all mutations identified in this cohort of patients have already been reported in the literature (Sterl et al 2012;Groselj et al 2012). However, the mutational spectrum was enlarged with seven mutations that were not reported in the previous study on Serbian population.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Unlike recent studies conducted in European PKU patients, all mutations identified in this cohort of patients have already been reported in the literature (Sterl et al 2012;Groselj et al 2012). However, the mutational spectrum was enlarged with seven mutations that were not reported in the previous study on Serbian population.…”
Section: Discussioncontrasting
confidence: 57%
“…According to the classification given in Sterl et al (2012), we classified all 39 Serbian PAH genotypes into BH4 responsive (26.2%), probably BH4 responsive (51%), and non-BH4 responsive (22.8%) (Table 3). Furthermore, we made distinction between genotypes with one and two BH4-responsive alleles.…”
Section: Bh4 Responsivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…The following studies attempted to predict BH4-responsiveness on the basis of single allele information or a patient's genotype (48,49,(67)(68)(69)(70)(71)(72)(73). For a number of patients' genotypes, the genotype-based prediction was found to be a useful complementary tool to the obligatory BH4 loading test.…”
Section: Bh4 Responsivenessmentioning
confidence: 99%